Miocardiopatia em cães naturalmente acometidos por leishmaniose visceral: aspectos histopatológicos e da resposta imune - Pacheco, Acácio Duarte [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
A ocorrência de miocardite em cães naturalmente acometidos por Leishmania infantum chagasi tem sido demonstrada em estudos recentes, contudo o tipo de resposta imune incitada no tecido cardíaco de cães com leishmaniose visceral (LV) ainda não foi determinada. Sendo assim, foram avaliados fragmentos da: parede livre de átrio direito (AD), parede livre de ventrículo direito (VD), parede livre de ventrículo esquerdo (VE) e septo interventricular (SIV) de 20 cães naturalmente acometidos por LV para determinação das alterações histopatológicas e da resposta imune no tecido cardíaco. A presença de miocardite foi observada em 75% dos animais avaliados, sendo o infiltrado inflamatório do tipo linfoplasmocitário a alteração mais comum nesses fragmentos. A imunomarcação de Leishmania spp. foi observada em 60% dos animais. Não houve correlação entre a intensidade do infiltrado inflamatório e a presença de Leishmania sp. no miocárdio (p=0,0682). A imunomarcação do parasito apresentou correlação com a presença de linfócitos T CD4+ (p<0,0001) e T CD8+ (p=0,0002), linfócitos B CD79+ (p=0,046) e IgG (p=0,040). Os níveis de IL-4 (p=0,030), IL-12 (p=0,002), IFN- (p<0,0001) foram menores em cães infectados em relação ao grupo controle, independente da presença ou não do parasito no miocárdio (p>0,05). No presente estudo, a presença de alterações miocárdicas, associadas a resposta imunológica mista foram comuns em cães com LV. Novos estudos avaliando paralelamente, a presença de inflamação miocárdica e o perfil de citocinas no tecido cardíaco, à resposta imunológica sistêmica são indicados para confirmação da resposta imunológica presente no miocárdio de cães acometidos por LV.

Recent studies have demonstrated the occurrence of myocarditis in dogs naturally infected with Leishmania infantum chagasi, however the type of immune response in cardiac tissue of dogs with visceral leishmaniasis (VL) has not been determined. For this purpose, fragments from right atrial free wall (AD), right ventricular free wall (RV), left ventricular free wall (LV) and interventricular septum (IVS) of 20 dogs naturally affected by VL were evaluated to determine the histopathological changes and the immune response in heart tissue. The presence of myocarditis has been reported in 75% of the evaluated animals, and an lymphoplasmocytic inflammatory infiltrate was the most common change in these fragments. The immunostaining of Leishmania sp. was observed in 60% of the evaluated animals. There was no correlation between the intensity of the inflammatory infiltrate and the presence of Leishmania sp. (p = 0.0682). The immunostaining of the parasite correlated with the presence of CD4 + (p <0.0001) and CD8 + T lymphocytes (p = 0.0002), CD79 + B lymphocytes (p = 0.046) and IgG (p = 0.040). IL-4 (p = 0.030), IL-12 (p = 0.002) and IFN- levels (p <0.0001) were lower in the infected dogs when compared to control group, regardless of the presence or absence parasite in the myocardium (p> 0.05). The results obtained in this study suggest that the presence of myocardial changes is common in dogs with VL, associated with a mixed immune response in heart tissue. However, the local inflammatory process seems not enough to trigger the production of cytokines normally involved in VL, possibly due to a low parasite load in dogs myocardium, especially when compared to other organs such as spleen, liver and bone marrow. Further studies evaluating at the same time the presence of myocardial inflammation and the behavior of these circulating cytokines in target organs with immune activity are indicated to confirm the immune response present in the myocardium of dogs affected by VL.
Miocardiopathy in dogs naturally affected by visceral leishmaniasis: histopathological patterns e immune response evaluation
Keywords: Linfócitos B CD79+; Linfócitos T CD4+; Linfócitos T CD8+; Citocinas; Leishmania spp.; Cytokines; T CD8+ lymphocytes; T CD4+ lymphocytes; B CD79+ lymphocytes